IMPACT OF MULTICULTURAL ENVIRONMENT OF INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA ON STUDENTS’ ACCULTURATION - Rahath House, Yousef; Abdul Razak, Mohd Abbas; Kazmi, Yedullah; Ashraf, Hiba (2016)
This research aimed to study the effect of exposure to Multicultural environment of educational institutions on the acculturation of its students. The study puts forth many types of research that show the positive effects of intergroup contact between groups of diverse ethnic backgrounds and cultural heritages in reducing prejudice and negative stereotyping towards the out-group. This study investigated whether or not the Internationalization process of the International Islamic University, Malaysia, with a multicultural environment, helps its students to, accept the differences that other cultures bring, be comfortable with differences and also seek diversity of contact. The study employed Miville-Guzman Universality – Diversity Scale, (M-GUDS-S) to collect data by survey method from 400 IIUM undergraduate students selected using Quota sampling. 200 of them were first-year students and the rest were fourth-year students. The result indicated that the multicultural environment at IIUM does lead to Acculturation among students. It showed that the fourth year students were significantly more appreciative of and comfortable with differences. However, in terms of seeking diversity of contact, there was no significant difference between first-year and fourth-year students. Based on the findings it has been suggested that if efforts are made to establish optimal conditions for positive intergroup contact to take place, intergroup prejudice can be reduced and problems of coexistence in the Muslim countries and communities can thus be addressed.